The effect of online customer reviews and sales promotion on interest in using the allo bank application for k-pop fans in Bandung City - Hasanah, Siti Uswatun; Suparwo, Adi; Drajat, Devi Yuniati; Handayani, Rina Dwi (Institute of Computer Science (IOCS), 2025)
Allo Bank is a bank with a strong K-pop image and is known to provide many sales promotions, but the Allo Bank application is ranked 10th with the lowest percentage of users among other digital banks. This study aims to ascertain how Bandung K-Pop fans' interest in using the Allo Bank application is influenced by online customer evaluations and sales incentives. This study utilizes quantitative research methods. The study's sample consists of 100 respondents who are K-Pop fans in Bandung and have never used the Allo Bank app. Purposive sampling, also known as non-probability sampling, is the sampling method used in this study. The IBM SPSS statistical software tool was utilized for the analysis of the gathered data. The findings showed that the variables of sales promotion and online customer review had a significant and partly favorable influence on the interest in using the Allo Bank application among K-POP fans in Bandung. Additionally, Bandung's K-Pop fans' interest in utilizing the Allo Bank application was impacted by both sales marketing and online customer reviews at the same time. Online customer reviews are useful because they are considered reliable and include a variety of comments, both positive, negative, and neutral. This provides a comprehensive overview of the Allo Bank app user experience before respondents can decide whether to use it. Future research could explore the inclusion of other influential elements, such as brand ambassadors, e-service quality, and customer experience